1996
DOI: 10.1083/jcb.135.4.913
|View full text |Cite
|
Sign up to set email alerts
|

Rab11 regulates recycling through the pericentriolar recycling endosome.

Abstract: Abstract. Small GTPases of the rab family are crucial elements of the machinery that controls membrane traffic. In the present study, we examined the distribution and function of rabll. Rabll was shown by confocal immunofluorescence microscopy and EM to colocalize with internalized transferrin in the pericentriolar recycling compartment of CHO and BHK cells. Expression of rabll mutants that are preferentially in the GTP-or GDP-bound state caused opposite effects on the distribution of transferrin-containing el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

93
1,147
6
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,208 publications
(1,261 citation statements)
references
References 55 publications
93
1,147
6
3
Order By: Relevance
“…Rather, some colocalization between the internal pool of Langerin, as revealed by the anti-lag mAb, and the LC marker CD1a was evident in the pericentriolar area ( Figure 1D). In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999 …”
Section: Langerin Is Associated With Rab11mentioning
confidence: 92%
“…Rather, some colocalization between the internal pool of Langerin, as revealed by the anti-lag mAb, and the LC marker CD1a was evident in the pericentriolar area ( Figure 1D). In another study carried out in the same cell type, we demonstrated that intracellular CD1a also colocalizes with Rab11 (Salamero et al, 2001), a small GTPase that specifically associates with the membrane of the endosomal recycling compartment (ERC) (Ullrich et al, 1996;Ren et al, 1998). Steady-state internal Langerin colocalized strongly with Rab11 in the ERC ( Figure 1E) but poorly with EEA1, a marker of the early/sorting endosomes ( Figure 1F) (Simonsen et al, 1998;Christoforidis et al, 1999;McBride et al, 1999 …”
Section: Langerin Is Associated With Rab11mentioning
confidence: 92%
“…Two candidate genes (RAB11A and MEGF11) were identified in the LD block of rs43616983. The gene RAB11A that encodes the Rab11A small GTPase, has been shown to play an important role in mediating transferrin recycling back to the plasma membrane and may play a role in innate immunity (Ullrich et al, 1996). A weak innate immune system has previously been documented to contribute to perinatal mortality (Kirkbride, 1993).…”
Section: Chromosome 18mentioning
confidence: 99%
“…The internalized surface components enter a complex and dynamic membrane system, the early endosome, which plays a vital role in sorting endocytosed proteins to different destinations in the cell (Gruenberg and Maxfield, 1995). It is now clear that the early endosome comprises at least two functionally distinct compartments or subdomains (Ghosh et al, 1994;Ghosh and Maxfield, 1995;Gruenberg and Maxfield, 1995;Ullrich et al, 1996;Zacchi et al, 1998). Markers first enter the early sorting endosome, a complex organelle with tubular and multivesicular domains, where membrane proteins destined for degradation are sorted away from those proteins, such as the transferrin receptor, that are recycled back to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%